Generalized selection of complementary matrices in the inclusion principle - Bakule, L.; Rodellar, J.; Rossell, J.M. (IEEE transactions on automatic control, 2000)
This paper presents a strategy for choosing complementary matrices in the framework of the inclusion principle with state LQ optimal control of LTI systems, it is based on translating the basic restrictions given by the inclusion principle into explicit block structures for these matrices, the degree of freedom given by these structures is illustrated by means of an example of overlapping decentralized control design.